Strategi Guru Pendidikan Agama Islam dalam Membina Kedisiplinan Peserta Didik di SMP N 4 Padang Kampung Pondok Kecamatan Padang Barat Kota Padang - Naibaho, Siti Hadijah; Rivauzi, Ahmad (ALSYS, 2024)
This study aims to determine the strategies of Islamic religious education teachers in fostering student discipline at SMP N 4 Padang Kampung Pondok, Padang Barat District, Padang City. This research is a qualitative approach research, data sources are taken from all informants using primary and secondary data. To obtain interview results, this study used interview guidelines as a research instrument. Data collection techniques used in this research are observation, interviews and documentation. As for the validity of the data that researchers use is triangulation (source triangulation and data triangulation) to produce data that can be accounted for. The results showed first, the PAI teacher's strategy in teaching discipline there are three teaching strategies used, namely making clear and comprehensive rules, strengthening character education programs, and building relationships approach. Second, the PAI teacher's strategy to foster student discipline awareness has two strategies in fostering student discipline awareness, namely through exemplary and training habituation. Third, the PAI teacher's strategy in supervising students' disciplinary behavior has three strategies, namely making a learning contract, applying punitive sanctions and rewarding.